MENYELARASKAN PIKIRAN DAN JIWA: MENGEKSPLORASI PERBEDAAN INDIVIDU DALAM KECERDASAN DAN KEPRIBADIAN DALAM KERANGKA PENDIDIKAN ISLAM - Poniran, Poniran; Jailani, Mohammad (JENTRE, 2023)
Intelligence and personality are gifts from Allah that share both similarities and differences, viewed from the perspective of Islamic Education Psychology. This research aims to explore the distinctions between the two. It is a systematic review conducted with a qualitative approach, drawing materials from various sources such as books, theses, journals, and reputable electronic resources. The findings reveal that there are commonalities and disparities between intelligence and personality according to Islamic Education Psychology. The similarities can be observed in the fundamental meanings of both terms and the aspects associated with them. In terms of their definitions, both have the root word 'aqal', which means acquiring knowledge for intelligence, while for personality, it serves as the foundation for behavior. As for their aspects, the difference lies in the fact that intellectual intelligence is utilized to develop one's intellect, while in personality, intellectuality determines behavioral patterns. Spiritual intelligence is employed to cultivate norms or values within oneself, whereas personality encompasses a person's inclination towards specific norms or values.